Functional Results of Cephalomedullary Nail Osteosynthesis of Transtrochanteric Fractures in Elderly Patients - Sulyma, V.S.; Valovina, Yu.D.; Sabsai, O.V.; Makarov, V.B.; Valovina, N.Yu.; Bihun, R.R.; Kuz , U.V. (TERRA ORTHOPAEDICA, 2021)
Summary. Relevance. Despite many surgical techniques that use modern metal fixators, treatment of elderly patients with fractures of the proximal part of the hip still remains relevant.Objective: to evaluate the functional results of surgical treatment of elderly patients with transtrochanteric fractures of the femur using a cephalomedullary locking nail (PFNA).Materials and Methods. The study involved 193 elderly patients (mean age 76.2±10.3 years) with transtrochanteric fractures of the femur type 31 A1-A2.1-1.3 (AO/OTA) after osteosynthesis by PFNA cephalomedullar fixator. The functional outcome of the treatment was determined after 1, 3, 12, and 36 months by Harris Hip Score (HHS), radiographic signs of bone union, and the presence of complications. The risk of recurrent trochanteric fractures over the next 10 years was calculated by adapted FRAX scale.Results. Positive changes were found by HSS, in the dynamics: 51.6 after 1 month, 60.2 after 3 months, 79.7 after 12 months, and 84.4 after 36 months. Within 6 months after the surgery, the following changes were found: secondary displacement of bone fragments with the “cut-out” eruption of the cervical blade in 2.3% (n=3), migration of the cervical component outward in 4.7% (n=6), and inflammation of surgical wound in 3.9% (n=5) of cases. Retrospectively, the average FRAX score was assessed (22.12±1.76).Conclusions. Stable functional osteosynthesis of transtrochanteric fractures of the femur using PFNA combined with early dosed loading on the injured limb allowed to obtain satisfactory functional results in 95.4% of cases. Secondary displacement of bone fragments with the “cut-out” effect requires a detailed analysis of all possible endo- and exogenous factors and identification of the most significant ones. The 10-year risk of recurrent fractures in patients with trochanteric fractures significantly increases over the age of 70, especially in females, and accounts for the majority of osteoporotic fractures.